Debris flows in the northern Tien Shan, Central Asia: regional database, meteorological triggers, and trends - Maria Shahgedanova; Zarina Saidaliyeva; Ainur Mussina; Vassily Kapitsa; Zhanar Raimbekova; Denis Donskikh; Daulet Kissebayev; Murat Kasenov; Maxim Petrov (npj Natural Hazards)
Abstract Debris flows, caused by Glacier Lake Outburst Floods (GLOF) or extreme weather, threaten lives and infrastructure in the northern Tien Shan. A geo-referenced database of 458 debris flow events of different geneses was compiled for the region. Between 1887 and 2020, there were 55 GLOF events, all resulting in debris flow formation. Their frequency peaked in the 1970s and declined afterwards. These events were associated with high air temperatures but not heavy rainfall. Debris flows unrelated to GLOFs were documented in the central Ile Alatau for the 1931–2020 period. They were predominantly caused by short-duration intense rainfall (pluvial debris flows) and/or intense glaciers and snowmelt. The median rainfall intensity triggering pluvial debris flows was 22–28 mm/day, depending on the catchment. There was no long-term trend in the frequency of pluvial debris flows, but their formation is increasingly observed at higher elevations.